2012
DOI: 10.1075/dia.29.4.04don
|View full text |Cite
|
Sign up to set email alerts
|

New methodologies for historical linguistics?

Abstract: Recent research claims that analysis of lexical cognate classes for a basic wordlist can reproduce linguistic subgroups within the Austronesian family (Gray et al. 2009). The analysis is open to question in two respects. Primarily, the lexicallybased classification, primed with pre-established cognate classes of the family it seeks to emulate, fails to differentiate shared retentions from shared innovations. Secondly, languages and language families typically disperse through contiguous regions (especially in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Trees with less than four leaves have identical topologies and thus cannot be used to recognize word borrowings [29]. It is important to note that the MLN approach is an automatic approach based on tree topology and the 42 suggestive cases of borrowing recovered by MLN, which include 33 English loanwords identified by Donohue et al [22], cannot be considered as crystal-clear borrowings. They may comprise some false positives, which can be due to parallel semantic development [21], for example.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Trees with less than four leaves have identical topologies and thus cannot be used to recognize word borrowings [29]. It is important to note that the MLN approach is an automatic approach based on tree topology and the 42 suggestive cases of borrowing recovered by MLN, which include 33 English loanwords identified by Donohue et al [22], cannot be considered as crystal-clear borrowings. They may comprise some false positives, which can be due to parallel semantic development [21], for example.…”
Section: Methodsmentioning
confidence: 99%
“…The loanword information was taken from the studies of Donohue et al ([22]; Supplementary Material) and List et al ([21]; modified MLN approach). To the 33 English loanwords identified by Donohue et al [22] and 8 possible additional English borrowings suggested by List et al ([21]; Supplementary Material II; Table C), we added the word dust , which might have been borrowed by English from Old North according to the results given by our algorithm for detecting word borrowing events [29]. This English word was also identified as belonging to an irregular pattern, which may be suggestive of borrowing, by the modified MLN approach [21].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…When we have no clear subgrouping available from the comparative method, as is the case for Albanian, an isolate within IndoEuropean, the language clusters with its geographic neighbors, and not as a distant branch on its own. While there is a clear genealogical stability associated with some typological features (as described and quantified in Wichmann and Holman, 2009), this may be inflated due to the high correlation that linguistic subgroups have with geography as well (as argued in Donohue et al, 2011, andDonohue et al, 2012). The reader can assess the geographic integrity of the clusters shown in Figure 2 by examining their mapping in Map 2, which shows the large-scale divisions of the languages.…”
Section: Test Case: Europe and The Balkan Linguistic Areamentioning
confidence: 96%